IMPLEMENTATION OF SMART SIM TO IMPROVE PUBLIC SERVICE QUALITY IN POLRES PURWAKARTA - Sulaiman, Arief (Police Studies Review, 2017)
Traffic Corps of Indonesian National Police (Korlantas Polri) launched innovation from drive license (SIM) card to become a Smart SIM card. Nowadays, a Smart SIM card embedded with a sophisticated and modern chipset to improve Indonesian National Police public service quality. The advantages of a Smart SIM card are it is connected to Smart SIM application in android smartphone, can store police forensic data, and able to do an electronic money transaction that cooperates with Bank Republik Indonesia (BRI). The problems in this research are, first, how do implementation of Smart SIM to improve public service quality in Polres Purwakarta. Second, what factors impact Smart SIM users on improving public service quality by Polres Purwakarta. The study was conducted at the resident unit of Satlantas Polres Purwakarta and used a qualitative method, which included interviews, observation, and document study. The writer adopts primary, secondary, and tertiary sources then validated with data triangulation. Afterward, using data reduction, data presentation, and concluding on data analysis techniques. Based on the results of the study, Satlantas Polres Purwakarta had issued a Smart SIM card product and sought to implement the Smart SIM excellent program. Although it has not yet run optimally due to obstacles encountered, such as problems in member's skills with Smart SIM technology, difficulty in accessing the Smart SIM application, and electronic money is still on the probational period. People of Purwakarta also have not been able to accept the innovations given because of the habit of citizens who rarely use internet access online. Therefore, the traffic record data cannot be accessed properly by the public, which then causes Purwakarta not be able to use this facility. The writer advises Korlantas Polri to monitor the use of Smart SIM in small areas, especially the West Java Regional Police (Polda Jawa Barat). Primarily for public services to achieve the prime service functions of the police, increase community satisfaction, and public trust. Key words: Implementation, Public service, Traffic corps, Smart SIM